(untitled) (Third Sector Social Economic Review, 2026)
Cultural heritage is an invaluable treasure inherited from the past, maintained in the present, and passed on to future generations. The Yezidis, one of the ancient peoples of Mesopotamia, have preserved their unique identity for centuries through a closed social structure and oral traditions. However, the 2014 attacks by ISIS (DAEŞ), subsequent forced displacements, and the pressures of modernization have led to a significant erosion of this cultural fabric. This study evaluates the tangible (architecture, cemeteries) and intangible (rituals, oral literature) elements of Yezidi cultural heritage within the framework of Community-Based Tourism (TTT) principles. The primary objective of the research is to develop a faith-based tourism model centered on cultural sustainability and the economic empowerment of local communities.